Stigma and Peer-Led Interventions: A Systematic Review and Meta-Analysis - Sun, Jing; Yin, Xunbao; Li, Changjiang; Liu, Wuyi; Sun, Hongwei (Frontiers in Psychiatry, 2022)
Purpose: The main purpose of our systematic review was to investigate the effect of peer-led intervention on self-stigma in individuals with mental health problems. Secondary purpose was investigating the impact of peer intervention on clinical symptoms, recovery-related outcomes, and disclosure-related outcomes. Methods: Five electronic databases were searched from 1975-2021. Literature databases were searched for randomized controlled trials. From the perspective of key outcomes, a meta-analysis of the effects of peer-led interventions on changing stigma was conducted. Results: A meta-analysis of randomized controlled trials targeting different target groups with mental health problems (e.g. adolescents, college students, family members of mentally ill persons, unemployed persons, etc.) was conducted. It was found that, at the end of the intervention, intervention had a positive effect on main outcomes such as self-stigma and stress from stigma. As for secondary outcomes, there was no significant influence on clinical symptoms, which is not statistically significant. There was a positive effect on rehabilitation and empowerment, but without a statistical significance. There was a statistically significant effect on self-efficacy and professional help seeking. There was a statistically significant effect on confidentiality and disclosure-related distress in the HOP subgroup. There was no significant influence on confidentiality and withdrawal in the non-HOP subgroup. Conclusion: Peer-led intervention can reduce self-stigma and stigma pressure and might improve recovery and empowerment. It increases self-efficacy and willingness to seek professional help, but has no significant effect on clinical symptoms and withdrawal. HOP intervention has positive effects on disclosure-related confidentiality and pain.